The HL-60 clone 15 cell line as a model for leukocyte migration–possibilities and limitations - Griesbaum, Lena; Weusthof, Christopher; Sauer, Thorben; Gemoll, Timo; Weirich, Gregor; Klimek, Ludger; Petry, Julie; Bashiri Dezfouli, Ali; Shoykhet, Maria; Wollenberg, Barbara (Frontiers in Immunology, 2025)
IntroductionAs a part of the innate immune system, eosinophils are recruited during infectious diseases, to release their characteristic cytotoxic granules and catch pathogens in extracellular traps. Moreover, eosinophils have a crucial role in autoimmune diseases, for example allergies. The isolation of these densest and lowest abundant leukocytes is cost-and labor intense. This sets restrictions on many aspects of eosinophilic research. In this study, we performed a thorough characterization and functional assessment of the HL-60 clone 15 (HC15) cell line, which can be differentiated into eosinophil-like cells, to investigate its potential in eosinophil research.MethodsHC15 cells were differentiated with sodium butyrate with or without IL-5 and cells were characterized and compared to primary eosinophils, neutrophils and peripheral blood mononuclear cells. Cell features were analyzed using proteomics, morphologic assessment, RT-qPCR, immunofluorescent staining and flow cytometry. Based on these results, functional tests were performed, including transwell migration assays, flow cytometry-based aggregate formation assays, immunofluorescent microscopy-based adherence assays to endothelial cells and flow cytometry- and ELISA-based activation assays.ResultsThe proteomes of the cell line cells differed from those of primary eosinophils and neutrophils. Differentiation of HC15 cells enhanced the expression of GATA-1 and altered the expression of surface markers IL-5R, EMR1, and TREM-1. Differentiated HC15 cells overexpressed the granule protein EPX compared to primary eosinophils and induced a distinct inflammatory milieu by secreting CCL-5, EPX and IL-8. The addition of IL-5 during differentiation increased this effect. Cell line cells responded weaker to activation than primary eosinophils but showed a similar migration and adherence pattern in multiple assays. These features were mostly unaffected by differentiation.DiscussionDifferentiation of HC15 cells induces an eosinophil lineage-committed precursor state. Hence, the differentiated cell line cells lacked characteristic features of eosinophils such as morphologic attributes, surface marker expression and the capacity to be activated. However, the cells were able to migrate, form aggregates with platelets and similarly adhere to endothelial cells as primary eosinophils. It is, therefore, advisable to use the cell line as an eosinophilic model only in research questions related to chemotaxis and migration.